Physical modeling of diesel generator exhaust dispersion: Limerick Generating Station unit 1 and 2, Philadelphia Electric Company - Poreh, Michael, author; Li, Wen-Whai, author; Cermak, Jack E., author; Peterka, Jon A., author; Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1985)
Dispersion of exhaust gases from the Diesel Generating Units in the Limerick Generating Station was simulated in the Environmental Wind Tunnel at Colorado State University, using a 1:110 scale model and the concentration levels and excess temperatures at the various air intakes were predicted for different wind directions and stack configurations. The maximum concentrations were found to occur at the air intakes of reactor enclosure buildings. The study shows that it is advantageous to eliminate the bend at the top of the present 7.5-ft stacks and exhaust the gases vertically, in order to reduce the concentration levels at the air intakes of the Reactor Enclosure Building. The maximum concentration levels at the various air intakes are shown to decrease with the height of the stacks and increase with the wind speed. For example, the dilution of the exhaust gases from 46 ft stacks was below 1/425 for southern wind speeds above 15 mph, whereas similar dilution of exhaust gases from 27.5-ft stacks occurred at southern wind speeds above 12 mph. The yearly probability of exceeding these wind speeds has been estimated, but it is recommended that the final choice of the stacks height be made after examining the possibility of establishing testing schedules for the diesel generators that will take advantage of low winds at the site. The maximum excess temperature at the Diesel Generator air intakes, was found to be 1°F, for the case of 2.5-ft stacks and high wind speeds from wind direction 292°.
CER84-85MP-WWL-JEC-JAP42.
February 1985.
CSU Project 2-96170.
Keywords: Philadelphia (Pa.) -- Buildings, structures, etc.; Wind tunnel models; Buildings -- Pennsylvania -- Philadelphia -- Aerodynamics